The ageing shift worker: a prospective cohort study on need for recovery, disability, and retirement intentions - Fleur Gommans; Nicole Jansen; Dave Stynen; Andries de Grip; IJmert Kant (Nordic Association of Occupational Safety and Health (NOROSH), 2015)
OBJECTIVES: This study investigates whether different shift work schedules, compared to day work, are associated with need for recovery (NFR), future disability, and retirement intentions for employees employed within different economic sectors over the course of their careers. Shift work exposure duration and the healthy worker effect are also examined. METHODS: Data from the prospective Maastricht Cohort Study was used. Subsamples of industry (N=1877, all men) and healthcare (N=818, 624 women and 194 men) workers were separately investigated. GEE and Cox regression analyses were performed to investigate NFR longitudinally. Future disability was investigated using Cox regression, and retirement intentions were investigated using logistic regression analysis. RESULTS: Three-shift industry workers were at risk of becoming a case of elevated NFR during follow-up, compared to industry day workers. Three- and five-shift industry workers were at risk for future disability. In healthcare, irregular shift work was a risk factor for disability among older shift workers. No significant results were found regarding retirement intentions. Findings were probably an underestimation as exposure duration to shift work and the healthy worker effect affected the results. CONCLUSIONS: Shift work was associated with higher levels of NFR and a higher risk of disability. However, shift work is a multifaceted concept as different types of shift work schedules are differently associated with these outcomes. Different shift work types exist and shift work schedules allow for optimization, indicating that measures to prevent adverse outcomes should be tailored for different types of shift work and over the course of the work career.